2006
DOI: 10.1039/b604856k
|View full text |Cite
|
Sign up to set email alerts
|

Contributions from radiation damping and surface scattering to the linewidth of the longitudinal plasmon band of gold nanorods: a single particle study

Abstract: The scattering spectra of single gold nanorods with aspect ratios between 2 and 4 have been examined by dark field microscopy. The results show that the longitudinal plasmon resonance (electron oscillation along the long axis of the rod) broadens as the width of the rods decreases from 14 to 8 nm. This is attributed to electron surface scattering. Analysis of the data using gamma = gamma(bulk) + Anu(F)/L(eff), where L(eff) is the effective path length of the electrons and nu(F) is the Fermi velocity, allows us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

50
445
4
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 300 publications
(500 citation statements)
references
References 38 publications
50
445
4
1
Order By: Relevance
“…31,34 As the size of the particles increases, coupling of the LSPR oscillation to the radiation field can become an important energy loss mechanism. 20,22,[32][33][34]46 This effect is known as radiation damping, and is not included in the above analysis. For spherical particles, radiation damping can be accounted for by using the full Mie theory expression to calculate the scattering cross-sections.…”
Section: Dephasing Processes In Metal Nanoparticlesmentioning
confidence: 99%
See 1 more Smart Citation
“…31,34 As the size of the particles increases, coupling of the LSPR oscillation to the radiation field can become an important energy loss mechanism. 20,22,[32][33][34]46 This effect is known as radiation damping, and is not included in the above analysis. For spherical particles, radiation damping can be accounted for by using the full Mie theory expression to calculate the scattering cross-sections.…”
Section: Dephasing Processes In Metal Nanoparticlesmentioning
confidence: 99%
“…33,34,46 For the nanorods, electron-surface scattering is the dominant effect for narrow rods (widths < 10 nm), and radiation damping dominates for thick rods (widths > 20 nm). 33 Rods with "in between" thicknesses have narrow resonances, which are essentially free from either radiation damping or electron-surface scattering effects.…”
Section: Introductionmentioning
confidence: 99%
“…Surface-assisted plasmon decay (Landau damping) has been extensively studied experimentally [33][34][35][36][37][38][39][40][41][42][43] and theoretically [44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59] since the pioneering paper by Kawabata and Kubo [44], who have shown that, for a spherical particle of radius a, the surface scattering rate is γ sp = 3v F /4a, where v F is the electron Fermi velocity. In subsequent quantum-mechanical studies carried within random phase approximation (RPA) [45][46][47][48][49][50][51] and timedependent local density approximation (TDLDA) [52][53][54][55][56][57][58][59] approaches, a more complicated picture has emerged involving the role of confining potential and nonlocal effects.…”
Section: Introductionmentioning
confidence: 99%
“…Different techniques are employed to characterize the particle morphology [24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39].…”
Section: Introductionmentioning
confidence: 99%
“…One direct and powerful technique is transition electron microscopy (TEM) [15,[28][29][30][31][32][33][34][35][36][37]40], but TEM suffers from the fact that sample preparation for three-dimensional TEM investigations is rather complicated and cannot be easily accomplished in situ. In addition, obtaining sufficient statistical data from TEM measurements is extremely time consuming.…”
Section: Introductionmentioning
confidence: 99%